KAMISHIBAI PHBS SEBAGAI METODE STORYTELLING UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 5 – 6 TAHUN DI TKIT LUQMANUL HAKIM INSAN MADANI BANDUNG: KAMISHIBAI PHBS SEBAGAI METODE STORYTELLING UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 5 – 6 TAHUN DI TKIT LUQMANUL HAKIM INSAN MADANI BANDUNG - Neny Widyana; Sya'bani, Diva Adellia; Sindi, Sindi Melani (JURNAL TERAS KESEHATAN, 2024)
Cognitive ability is one aspect of early childhood development that needs to be stimulated from an early age. This research aims to determine the application of kamishibai as a medium used in storytelling to improve the cognitive abilities of children aged 5 - 6 years. This study used a one-group pretest-posttest design, measuring cognitive abilities before and after intervention. The subjects of this research were 25 students aged 5 - 6 years at Luqmanul Hakim Insan Madani Kindergarten, Bandung. The results of research on the Pretest show that children's cognitive abilities 57,7 % with Developing According to Expectation (BSH) criteria. Meanwhile, the Posttest shows that the child's cognitive abilities have increased to 79,3% with the criteria of Very Well Developed (BSB). Based on the results of this research, it can be said that the Storytelling Method using Kamishibai can improve children's cognitive abilities.